The Non-Human Animal - Mingote Ferreira de Azara, Michel (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2013)
The story “Meu tio, o Iauretê” (1962 ), from Guimarães Rosa, discusses the boundary between man and animal, through intensive writing, which seeks to unveil the animal in man. Thus, thinking animalism in Guimarães Rosa, means thinking what the French philosopher Gilles Deleuze would call “Becoming – Animal” which concept is present in a text from 1730 - Becoming - Intense, Becoming - Animal, Becoming – imperceptible…, and would be an order of combination of a man with an animal, none of which would be similar or even copy each other, in other words, it would not be a matter of metamorphosis, but becomings, crossings and short circuit between kingdoms. In this sense, the philosophy of Gilles Deleuze, Jacques Derrida and Georges Bataille serve as a basic scope to reflect on the question of self and other, man and animal, identity and difference. The questioning of this issue, through literature, aims to demonstrate how to give, in literary narrative, language, questioning of anthropocentrism, in the words of Derrida’s “own man”, which would result in the subsumption on power of life, pure, immanent.